Comparison of eating habits between students of AWF Biała Podlaska and students of AWFiS Gdansk - Piątek, Mirosław; Byzdra, Krzysztof; Mikołajczyk, Janusz; Stępniak, Robert (Journal of Education, Health and Sport, 2017)
The main goal of work was qualitative and quantatitive comprasion of eating habits between students of AWF Biała Podlaska and students of AWFiS Gdansk. The main portrayal and comprasion of level that analysed students use their knowledge In terms of diet. The main experimental questions were: 1. How many meals do the students have during the day? 2. What was the frequency of eating given meals by tested groups? 3. How does the final quantitative result of eating habits look like? In the study participated students and F Biała Podlaska and students AWFiS Gdańsk. In the study were men and women. A total of 160 were investigated. The first group of students were surveyed during January and February 2015. It was a group of students Academy of physical education in Biała Podlaska. A total of 80 examined people. The male sex represented 52 students, which represented 65% of the group, while the female sex represented 28 female students, which accounted for 35% of the group. The average age of the subjects was 21.5 years. Average weight in males was 73 kg and women’s 59 kg. Academic youth sports in the correct way to use the knowledge gained at the Academy of physical education. His person, as future teachers of physical education, well show a positive attitude toward healthy lifestyles, as well as take into account the proper eating habits. Students of sports colleges were well prepared to promote a healthy lifestyle, what with a methodical point of view is a successful University.